Artificial Intelligence and Human Consciousness: Philosophical and Religious Perspectives - Promkun, Suraphon (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2025)
This paper explores the philosophical and religious perspectives on artificial intelligence (AI) and human consciousness, examining the implications of AI’s evolving capabilities in relation to self-awareness, moral agency, and spiritual identity. The rapid development of AI raises fundamental questions about the nature of consciousness, challenging long-held philosophical distinctions between mind and matter, as well as theological concepts of the soul. Drawing from diverse philosophical traditions, including dualism, emergentism, and physicalism, this study investigates whether AI can possess consciousness or merely simulate human cognitive processes. Additionally, the paper discusses religious interpretations of AI’s role in human life, considering perspectives from Buddhism, Christianity, and other spiritual traditions regarding the ethical implications of machine intelligence. Through an interdisciplinary approach, this paper aims to deepen the understanding of AI’s impact on human identity, free will, and moral responsibility. Ultimately, it calls for a balanced integration of technological advancements with ethical and spiritual considerations to navigate the challenges posed by AI in contemporary society.